Molecular Layer‐by‐Layer Assembled Thin‐Film Composite Membranes for Water Desalination. (12th July 2013) - Gu, Joung‐Eun; Lee, Seunghye; Stafford, Christopher M.; Lee, Jong Suk; Choi, Wansuk; Kim, Bo‐Young; Baek, Kyung‐Youl; Chan, Edwin P.; Chung, Jun Young; Bang, Joona; Lee, Jung‐Hyun
<x xml:space="preserve">Abstract</x> Molecular layer‐by‐layer (mLbL) assembled thin‐film composite membranes fabricated by alternating deposition of reactive monomers on porous supports exhibit both improved salt rejection and enhanced water flux compared to traditional reverse osmosis membranes prepared by interfacial polymerization. Additionally, the well‐controlled structures achieved by mLbL deposition further lead to improved antifouling performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>